The leading factors of working at height's accident among construction workers in Kota Bharu, Kelantan - Khalil, Nor Alwani (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2016)
Nowadays, the accident rate when working at high places is a concern. The aim of this research was to study the factors that lead to accident while working at height among construction workers in Kota Bharu, Kelantan. This study was conducted in order to identify the relationship between age, working condition and work procedure with accident during working at height. There were on 90 workers at a construction site become a respondent. The questionnaire was used in this study which consists of section A (demographic data), section B (working condition) and section C (work procedure). A Chi Square test, Pearson Correlation test and Spearman Correlation test were used to answer the objectives of the study. The finding showed that there were significance for relationship between work procedures with accident during working at height for Spearmen Correlation test (p = 0.019). However, there were no significance relationship between age (p = 0.144), working condition (p = 0.117), (p = 0.685) and work procedure (p = 0.097) with accident during working at height. Factor of accidents due to working at height among construction workers in Kota Bharu, Kelantan was found related to the work procedure. Therefore, to reduce the accidents from occurring due to working procedure, the initial steps such as ensure the workers wear personal protective equipment should be taken. Besides that, inspection and maintenance of equipment should be emphasized to reduce the risk of fall among the workers.